A systematic review and metanalysis of questionnaires used for auditory processing screening and evaluation - Samara, Myrto; Thai-Van, Hung; Ptok, Martin; Glarou, Eleni; Veuillet, Evelyne; Miller, Simone; Reynard, Pierre; Grech, Helen; Utoomprurkporn, Nattawan; Sereti, Afroditi; Bamiou, Doris-Eva; Iliadou, Vasiliki Maria (Frontiers in Neurology, 2023)
The recognition of Auditory Processing Disorder (APD) as a distinct clinical condition that impacts hearing capacity and mental health has gained attention. Although pure tone audiometry is the gold standard for assessing hearing, it inadequately reflects everyday hearing abilities, especially in challenging acoustic environments. Deficits in speech perception in noise, a key aspect of APD, have been linked to an increased risk of dementia. The World Health Organization emphasizes the need for evaluating central auditory function in cases of mild hearing loss and normal audiometry results. Specific questionnaires play a crucial role in documenting and quantifying the difficulties faced by individuals with APD. Validated questionnaires such as the Children’s Auditory Processing Performance Scale, the Fisher’s Auditory Problems Checklist, and the Auditory Processing Domains Questionnaire are available for children, while questionnaires for adults include items related to auditory functions associated with APD. This systematic review and meta-analysis identified six questionnaires used for screening and evaluating APD with a total of 783 participants across 12 studies. The questionnaires exhibited differences in domains evaluated, scoring methods, and evaluation of listening in quiet and noise. Meta-analysis results demonstrated that individuals with APD consistently exhibited worse scores compared to healthy controls across all questionnaires. Additionally, comparisons with clinical control groups showed varying results. The study highlights (i) the importance of standardized questionnaires in identifying and assessing APD, aiding in its diagnosis and management, and (ii) the need to use sub-scores as well as overall scores of questionnaires to elaborate on specific hearing and listening situations. There is a need to develop more APD specific questionnaires for the adult population as well as for more focused research on APD diagnosed individuals to further establish the validity and reliability of these questionnaires.